Živa pripoved v zapisu Kontekst, tekstura in prekodiranje pripovedi Tine Kravanja iz Bavšice - Ivančič Kutin, Barbara (Ethnologica - Dissertationes, 2011)
The scientific monograph ('A Written Record of Live Storytelling') brings the basic theory and methodological procedures for field documentation, transcription and research of narrative folklore. It addresses threeContext, Texture and Transcoding of Stories Told Live by Tina Kravanja from Bavšica" brings the basic theory and methodological procedures for field documentation, transcription and research of narrative folklore. It addresses three levels of a folklore event - context, texture, and text - in the narration of folklore stories. Each level, especially context, is further enhanced with the theoretical findings derived from the author's own field work, e.g. defining storytelling meeting as alternation of stories, told in more artistic expression, and of linking texts told in an everyday. Linking texts are important cohesive ties of storytelling event as whole. The book also deals with defining of six roles of the participants who influence the course of storytelling event, etc. The monograph also attempts to solve the problem of putting down oral stories onto paper. To preserve as much information as possible, it proposes transcription as well as transcoding with the help of accurate phonetic transcription, concurrent notes on the texture, and a description of the context. The methods are explained with the phonetic transcription of 22 stories told by Tina Kravanja from Bavšica during a single field visit.